2013
DOI: 10.1371/journal.pone.0083978
|View full text |Cite
|
Sign up to set email alerts
|

Expression of DNA Translesion Synthesis Polymerase η in Head and Neck Squamous Cell Cancer Predicts Resistance to Gemcitabine and Cisplatin-Based Chemotherapy

Abstract: PurposeThe development of resistance against anticancer drugs has been a persistent clinical problem for the treatment of locally advanced malignancies in the head and neck mucosal derived squamous cell carcinoma (HNSCC). Recent evidence indicates that the DNA translesion synthesis (TLS) polymerase η (Pol η; hRad30a gene) reduces the effectiveness of gemcitabine/cisplatin. The goal of this study is to examine the relationship between the expression level of Pol η and the observed resistance against these chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 51 publications
1
49
3
Order By: Relevance
“…Cisplatin treatment efficacy is inversely correlated to the expression level of Pol η in various cancers (30)(31)(32). To determine whether Pol η down-regulation affects the efficacy of cisplatin treatment in ovarian cancers, we established a 2008 cell line with Pol η stable knockdown and generated xenografts by injecting cells s.c. into Athymic nude mice.…”
Section: Cd117mentioning
confidence: 99%
“…Cisplatin treatment efficacy is inversely correlated to the expression level of Pol η in various cancers (30)(31)(32). To determine whether Pol η down-regulation affects the efficacy of cisplatin treatment in ovarian cancers, we established a 2008 cell line with Pol η stable knockdown and generated xenografts by injecting cells s.c. into Athymic nude mice.…”
Section: Cd117mentioning
confidence: 99%
“…It is not clear from the available literature whether patients with XP-V are prone to the development of obesity and the metabolic syndrome. Given that variation in the expression level of the XP-V gene affects the sensitivity to DNA-damaging agents in various tissues (10,(38)(39)(40), an epidemiological study will be necessary to examine the correlation between the pol η expression level and the metabolic syndrome. In addition to pol η, other translesion synthesis polymerases have been shown to handle various types of DNA lesions (41), and it will be interesting to determine whether KO mice for other lesion bypass polymerases are prone to obesity and metabolic abnormalities.…”
Section: Impact Of Pol η On Cellular Senescence and Adipogenesis Usingmentioning
confidence: 99%
“…Using a nanoparticle-based platform engineered to codeliver cisplatin and Rev1/Rev3-specific siRNAs, Xu et al demonstrated synergistic inhibition of tumor growth in a human prostate cancer xenograft model [95]. Pol η expression was found to be elevated in 67% of head and neck cancers compared to normal tissue [96]. Alterations in Pol η expression have been correlated with response to platinum based chemotherapy.…”
Section: Fa/brca/hrr/tls Crosstalk and Chemoresistancementioning
confidence: 99%
“…Alterations in Pol η expression have been correlated with response to platinum based chemotherapy. Low levels of Polη have been associated with better prognosis, and its expression status considered as a potential marker for platinum therapy effectiveness [96]. The involvement of TLS polymerases in chemoresistance offers further proof that error-prone polymerases are crucial for filling gaps caused by chemotherapeutic drugs, thus providing a novel framework for development of therapeutics with chemosensitization potential.…”
Section: Fa/brca/hrr/tls Crosstalk and Chemoresistancementioning
confidence: 99%